Both of the previous answers are correct. If you prefer to eliminate y first, you notice the first equation has addition and the second subtraction. Mulitply the first equation by 2 and the second by 5. When you add the two new equations together you will see that the y terms cancel and you are left with a simple equation in x.
Solve for x. Substitute the value of x in either of the original equations and you have a simple equation in y to solve for that variable. The solution to the system of equations is the coordinate pair (x, y).
2x+5y = 14 ---equation 1
3x-2y= -36 ----equation 2
multiply eq. 1 by (-3) and eq.2 by 2 and add the two equations-
-6x - 15 y = -42
6x-4y = -72
-19y =- 114
y = 6
2x + 5*6 = 14
2x = 14-30 = 16
x = -8
Multiply each term in the first equation by 3 and each term in the second equation by 2.
Then subtract the second from the first. This will give you one equation in one variable (y).
Solve for y.
Then substitute that value into either equation and solve for x.